KARAKTERISASI SIFAT MEKANIK DAN STRUKTUR MIKRO PADA BAJA PADUAN RENDAH HASIL PROSES HARDENING - Moch. Chamim; Margono Margono; Fatimah Nur Hidayah; Nugroho Tri Atmoko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The purpose of this study was to determine how the mechanical properties and microstructure formed on low alloy steel (tooth bucket) heated at temperatures of 850 ⁰C and 850 ⁰C then held for 15 minutes after that it was cooled with oil. The material hardening process was carried out by testing the Vickers hardness, impact, and observing the microstructure using an optical microscope with 200x magnification. Hardness values obtained from low alloy steel after heat treatment at temperatures of 800 ⁰C and 850 ⁰C are 389.2 HV and 414.6 HV. The optimum hardness is obtained at a temperature of 850 ⁰C with an increase of about 1.14% compared to that of raw material, which is 364.5 HV. From the results of the impact test on heat treatment with a temperature of 850 ⁰C, the highest impact value is 0.574 Joule/mm2. Furthermore, the results of the microstructure on heat treatment at a temperature of 850 ⁰C resulted in homogeneous microstructures, namely chrome, martensite, and bainite.